CONSTRUCTION OF CONTEMPORARY CONTINUOS PROFESSIONAL EDUCATION: COMPARATIVE DISCOURSE - Roliak, Angelina (Sworld-Us Conference proceedings, 2022)
The article deals with the problem of up-to-date model of professional development training creation in the context of European and Ukrainian educational environments. On the basis of main international and national documents analysis on professional trai